2022
DOI: 10.1093/cid/ciac783
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Extended Treatment With Artemether-lumefantrine on Antimalarial Exposure and Reinfection Risks in Ugandan Children With Uncomplicated Malaria: A Randomized Controlled Trial

Abstract: Background. Artemether-lumefantrine (AL) is the most widely used artemisinin-based combination therapy (ACT) in sub-Saharan Africa and is threatened by the emergence of artemisinin resistance. Dosing is suboptimal in young children. We hypothesized that extending AL duration will improve exposure and reduce reinfection risks. Methods. We conducted a prospective, randomized, open-label pharmacokinetic/pharmacodynamic study of extended duration AL (EXALT) in children with malaria in high transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…Studies of asymptomatic individuals with consecutive daily sampling noted complex fluctuations in daily parasite clones and densities, reinforcing our understanding that any given sample represents only a fraction of the total parasite population 52 54 . Consistent with studies showing that size polymorphism-based genotyping typically underestimates MOI, we previously reported a pre-treatment median of 3 clones using only msp2 in this same cohort of HIV-uninfected children 42 , 55 58 .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Studies of asymptomatic individuals with consecutive daily sampling noted complex fluctuations in daily parasite clones and densities, reinforcing our understanding that any given sample represents only a fraction of the total parasite population 52 54 . Consistent with studies showing that size polymorphism-based genotyping typically underestimates MOI, we previously reported a pre-treatment median of 3 clones using only msp2 in this same cohort of HIV-uninfected children 42 , 55 58 .…”
Section: Discussionsupporting
confidence: 87%
“…We previously showed that extending AL from a 3 day to a 5 day regimen significantly improved artemether and lumefantrine drug exposure in children 42 . Despite this improved exposure, extending the duration (and number of doses) of AL was unable to significantly reduce the risk of recurrent parasitemia as defined by microscopy.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations